Break Even Point Nilai Ekonomis Gula Aren (Arenga pinnata Merr.) - Bahrun, Bahrun; MW, Yayuk (​Institute for Researches and Community Services Universitas Muhammadiyah Palangkaraya, 2024)
Research to determine the processing process, costs, revenues, profits, and break-even point (BEP) of the palm sugar processing business. The research was carried out in Ida Manggala Village, Sungai Raya District, Hulu Sungai Selatan Regency. The data used consists of primary data and secondary data. Determining the number of respondents was carried out using the census method by taking all samples from the population (4 respondents). Production during one production period (1 month) was an average of 267.73 kg/per month, with the price in effect at the time of the study Rp. 15,000/kg. Average revenue is IDR. 4,015,875/month. Average total cost is 2,243,874.54/person. Calculation of BEP value is based on the average production amount (unit) of 13.85 kg/farmer. The BEP value is based on average sales of Rp. 220,914.59.